2004
DOI: 10.1152/ajpheart.00486.2004
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage: cardiovascular consequences of chronic sympathetic activation with human aging

Abstract: Adult aging in humans is associated with marked and sustained increases in sympathetic nervous system (SNS) activity to several peripheral tissues, including the heart, the gut-liver circulation, and skeletal muscle. This chronic activation of the peripheral SNS likely is, at least in part, a primary response of the central nervous system to stimulate thermogenesis to prevent further fat storage in the face of increasing adiposity with aging. However, as has been proposed in obesity hypertension, this tonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 78 publications
7
82
0
4
Order By: Relevance
“…The elevation in blood pressure with age is attributable, at least in part, to an increase in sympathetic nervous activity (Esler M. et al, 2002;Esler M.D. et al, 1995;Seals and Dinenno, 2004), and sustained elevation of catecholaminergic activity requires increased levels of catecholamine biosynthesizing enzymes in the adrenal medulla and peripheral sympathetic ganglia. Our laboratory along with others have reported that TH and DβH mRNA, protein levels and enzyme activities are two-to three-fold higher in the adrenals of senescent rats compared with younger animals (Banerji et al, 1984;Kedzierski and Porter, 1990;Tumer et al, 1999;Tumer et al, 1992;Tumer and Larochelle, 1995;Voogt et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The elevation in blood pressure with age is attributable, at least in part, to an increase in sympathetic nervous activity (Esler M. et al, 2002;Esler M.D. et al, 1995;Seals and Dinenno, 2004), and sustained elevation of catecholaminergic activity requires increased levels of catecholamine biosynthesizing enzymes in the adrenal medulla and peripheral sympathetic ganglia. Our laboratory along with others have reported that TH and DβH mRNA, protein levels and enzyme activities are two-to three-fold higher in the adrenals of senescent rats compared with younger animals (Banerji et al, 1984;Kedzierski and Porter, 1990;Tumer et al, 1999;Tumer et al, 1992;Tumer and Larochelle, 1995;Voogt et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 But chronically raised MSNA also occurs during aging and is accompanied by reduced reflex vasoconstriction and loss of NPY involvement in skin. 13,14 However, in young men at high altitude, chronic hypoxia caused an increase in tonic MSNA, tonic muscle vasoconstriction, and hypertension that persisted on descent to sea level. 15,16 Further, vasoconstrictor responses evoked by sympathetic activation were blunted in acute and chronic hypoxia in adult rats and humans [17][18][19] ; this was attributed to impaired vasoconstriction to NE and adenosine triphospate, but preservation of the NPY component.…”
mentioning
confidence: 99%
“…It is well established that elevated vasoconstrictor tone as a consequence of high sympathetic nerve activity is present in healthy, older adults, [7][8][9] despite a reduction in the sensitivity of postjunctional adrenergic vascular receptors. 10 This capacity for sustained sympathetic vasoconstriction in the face of reduced adrenergic responsiveness may be suggestive of an age-related change in nonadrenergic vasoconstrictor pathways, such as Ang II.…”
mentioning
confidence: 99%